Copper-decorated strategy based on defect-rich NH2-MIL-125(Ti) boosts efficient photocatalytic degradation of methyl mercaptan under sunlight - He,L; Xu,Y; Yang,Z; Lu,X; Yao,X; Li,C; Xu,D; Wu,C; Yao,Z (Environmental Pollution, 2024)
Photocatalysis has received significant attention as a technology that can solve environmental problems. Metal-organic frameworks are currently being used as novel photocatalysts but are still limited by the rapid recombination of photogenerated carriers, low photogenerated electron migration efficiency and poor solar light utilization rate. In this work, a novel photocatalyst was successfully constructed by introducing Cu species into thermal activated mixed-ligand NH2-MIL-125 (Ti) via defect engineering strategy. The constructed defect structure not only provided 3D-interconnected gas transfer channels, but also offered suitable space to accommodate introduced Cu species. For the most effective photocatalyst 0.2Cu/80%NH2-MIL-125 (300 °C) with optimized Cu content, the photocatalytic degradation rate of CH3SH achieved 4.65 times higher than that of pristine NH2-MIL-125 under visible light (λ > 420 nm). At the same time, it showed great degradation efficiency under natural sunlight, 100 ppm CH3SH was completely removed within 25 min in full solar light illumination. The improved catalytic efficiency is mainly due to the synergistic effect of the integrated Schottky junction and rich-defective NH2-MIL-125, which improved the bandgap and band position, and thus facilitated the separation and transfer of the photo-generated carriers. This work provided a facile way to integrate Schottky junctions and rich-defective MOFs with high stability. Due to its excellent degradation performance under sunlight, it also offered a prospective strategy for rational design of high-efficiency catalysts applied in environmental technologies.